Twin Pregnancy With Two Live Fetuses at 11–13 Weeks: Effect of One Fetal Death on Pregnancy Outcome. Issue 9 (September 2020) - Cimpoca, B.; Syngelaki, A.; Mu, A. Chi; Savvoulidou, E.; Nicolaides, K. H.
Abstract : (Abstracted from Ultrasound Obstet Gynecol 2020;55:482–488) Monochorionic (MC) and dichorionic (DC) twin pregnancies have been associated with higher rates of fetal loss, perinatal death, and early preterm birth. A previous systematic review of 16 studies reported that the risk of death of the cotwin in pregnancies with a single fetal death was 13.4% in 149 MC and 3.0% in 166 DC pregnancies.